MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN DENGAN LESSON STUDY DI KELAS SD NEGERI 001 KOTO PERAKU KECAMATAN CERENTI - Karmizan Karmizan (Jurnal PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the low pedagogical competence of teachers in the making of learning implementation plan, implementation of learning process, and implementation of learning evaluation. The purpose of this research is to improve teacher pedagogic competence. This research is located at SD Negeri 001 Koto Peraku Kecamatan Cerenti. The design of this study used a school action research consisting of 2 cycles. The results of the research show that the assessment of the making of the implementation plan of learning in cycle I get the value of 74.88 with enough category, in the second cycle increased to 84.96 with good category. the assessment of the learning process in cycle I get the value of 76.75 with good category, in cycle II to 86.04 with very good category. Assessment on the implementation of the evaluation of learning in cycle I obtained a score of 81.13 with good category, in cycle II to 88.48 with very good category. Based on the results of this study, using Lesson Study can improve pedagogic competence of teachers in learning mathematics in the SD Negeri 001 Koto Peraku Kecamatan Cerenti.